What matters to patients? A mixed method study of the importance and consideration of oncology patient demands - Mathias WAELLI; Etienne Minvielle; Maria Ximena Acero; Khouloud Ba; Benoit Lalloué (BMC, 2021)
Abstract Background A patient-centred approach is increasingly the mandate for healthcare delivery, especially with the growing emergence of chronic conditions. A relevant but often overlooked obstacle to delivering person-centred care is the identification and consideration of all demands based on individual experience, not only disease-based requirements. Mindful of this approach, there is a need to explore how patient demands are expressed and considered in healthcare delivery systems. This study aims to: (i) understand how different types of demands expressed by patients are taken into account in the current delivery systems operated by Health Care Organisations (HCOs); (ii) explore the often overlooked content of specific non-clinical demands (i.e. demands related to interactions between disease treatments and everyday life). Method We adopted a mixed method in two cancer centres, representing exemplary cases of organisational transformation: (i) circulation of a questionnaire to assess the importance that breast cancer patients attach to every clinical (C) and non-clinical (NC) demand identified in an exploratory inquiry, and the extent to which each demand has been taken into account based on individual experiences; (ii) a qualitative analysis based on semi-structured interviews exploring the content of specific NC demands. Results Further to the way in which the questionnaires were answered (573 answers/680 questionnaires printed) and the semi-structured interviews (36) with cancer patients, results show that NC demands are deemed by patients to be almost as important as C demands (C = 6.53/7 VS. NC = 6.13), but are perceived to be considered to a lesser extent in terms of pathway management (NC = 4.02 VS C = 5.65), with a significant variation depending on the type of non-clinical demands expressed. Five types of NC demands can be identified: demands relating to daily life, alternative medicine, structure of the treatment pathway, administrative and logistic assistance and demands relating to new technologies. Conclusions This study shows that HCOs should be able to consider non-clinical demands in addition to those referring to clinical needs. These demands require revision of the healthcare professionals' mandate and transition from a supply-orientated system towards a demand-driven approach throughout the care pathway. Other sectors have developed hospitality management, mass customisation and personalisation to scale up approaches that could serve as inspiring examples.